Sub-chronic toxicity of broflanilide on the nervous system of zebrafish (Danio rerio). Issue 2 (7th February 2023) - Wang, Kai; Qi, Zhiqiu; Duan, Manman; Zhang, Ru; He, Lu
ABSTRACT: The new insecticide broflanilide, which possesses high insecticidal activity against agricultural pests, acts on the γ-aminobutyric acid receptor in the insect nervous system. At present, few studies assessed its effect on the nervous system of zebrafish, especially its sub-chronic toxicity on the zebrafish brain. In this study, the sub-chronic toxicity of broflanilide on the zebrafish brain was assessed. After 21 days of exposure at 36.3 μg/L, broflanilide caused oxidative damage to the zebrafish brain, increased the levels of reactive oxygen species and malondialdehyde, and inhibited the activities of superoxide dismutase, catalase, and glutathione peroxidase. Overall, these changes result in brain cell apoptosis, and inhibited growth and development. Moreover, broflanilide affects the release of acetylcholinesterase, γ-aminobutyric acid, 5-hydroxy tryptamine, and dopamine as well as the expression of related genes in the brain, leading to abnormal zebrafish behaviour. These results corroborate the sub-chronic toxicity of broflanilide on zebrafish brain, which helps the further understanding of the potential environmental risk of broflanilide.